Distribution of Macrolides Resistant Genes among Local Clinical Isolates of Enterococcus spp. from Root Canal and Urine Samples - Molan, Nabaa Kamil; Hussein, Alyaa Razooqi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Gram-positive enterococci are opportunistic and resistant to many antibiotics. This search investigated the prevalence of macrolide antibiotic resistance genes in local enterococcal isolates and its correlation with biofilm formation. We collected 112 clinical samples from the Medical City Hospital, dentists' clinics, and labs in Baghdad from October 2022 to March 2023, which included root canal samples from 50 patients and urine samples from 62 patients with urinary tract infections. The samples were cultured on Pfizer-specific Enterococcus media. Twenty-one isolates were identified as Enterococcus spp. by biochemical tests and confirmed using the VITEK 2 system. After that, the crystal violet staining method was used to assess enterococci isolates' ability to form biofilms in a polystyrene microtiter, and then molecular detection was done to detect the ermB gene. The results revealed that the percentage of enterococcal isolates positive for the ermB gene was 87.5% in root canal samples. In urine samples, the percentage of enterococcal isolates with the same gene was 84.6%. All isolates succeeded in forming biofilm; for urine isolates, 77% and 23% of isolates formed moderate and strong biofilm, respectively. While for root canal isolates, 12.5%, 75%, and 12.5% of isolates formed weak, moderate, and strong biofilm, respectively. We conclude in this study that the ermB gene was detected in enterococcal isolates from the tooth root canal and urine samples, with a higher prevalence percentage in urine sample isolates than tooth root canal isolates. Finally, the findings demonstrated that there is no connection between this gene's existence and the tested isolates' ability to create biofilms.